Imperial Prune Company fruit drying yard and orchards - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic view of the Imperial Prune Company fruit drying yard and buildings. Several stacks of boxes with the Imperial Prunes label are visible. On the far right of the drying yards are orchards and and several production buildings. On the far left, several male workers are standing next to a packing building.